2014
DOI: 10.5195/jyd.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Program Innovations and Character in Cub Scouts: Findings from Year 1 of a Mixed-Methods, Longitudinal Study

Abstract: Youth development programs seek to promote positive development through mentoring and engaging youth in opportunities for individual growth and community connectedness. We present findings from the initial phase of a mixed-methods, longitudinal study aimed at assessing the impact of one such program, Cub Scouts, on character development. We assessed if Scouting, and a recent innovation in Scouting focused on program quality, are associated with the development of character and other positive youth outcomes. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…BSA programmatic influences on leaders’ beliefs have previously been identified in research. For example, Hilliard et al (2014) found the BSA’s conception of character informed leaders’ beliefs and actions related to character-building. However, when this study’s participants identified challenges in working with adolescents, they framed these challenges as characteristics or attributes of their adolescent scouts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BSA programmatic influences on leaders’ beliefs have previously been identified in research. For example, Hilliard et al (2014) found the BSA’s conception of character informed leaders’ beliefs and actions related to character-building. However, when this study’s participants identified challenges in working with adolescents, they framed these challenges as characteristics or attributes of their adolescent scouts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of BSA programs, particularly the BSA’s program for 6 to 10 year-olds called Cub Scouts, have highlighted leaders’ roles and perceptions of their influence on youth. Cub Scout leaders have been identified as positive role models who actively promote character development in youth (e.g., Hershberg et al, 2015; Hilliard et al, 2014; Wang et al, 2017). Participants in these studies offer explanations for how or why Scouting influences positive youth development for pre-adolescents, yet they seldom discuss their contributions beyond character development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, developmental theories predicated on RDS metatheory-based ideas suggest that OST youth development programs may be an important context for character development and education because of the positive, mutually influential relations between youth and adult leaders found in exemplary instantiations of such programs (Hilliard et al, 2014;Lerner & Callina, 2014;Vandell et al, 2015). Accordingly, research about the role of OST youth development programs, including evaluations of specific programs, is burgeoning in relation to increased interest in RDS-based models of human development (Lerner, 2015), to the fact that each of tens of millions of American youth participate in several OST programs each years (Vandell et al, 2015), and to heightened emphasis among scientists, educators, and policy makers about the importance of promoting character among the diverse youth of the nation (Berkowitz, 2011(Berkowitz, , 2012.…”
Section: Relational Developmental Systems Metatheory and The Study Ofmentioning
confidence: 99%
“…Increasingly, attributes of character -for instance, moral virtues (e.g., integrity, justice, caring, and respect), performance character (e.g., effort, diligence, perseverance, grit, and self-discipline), civic character (e.g., the knowledge, skills, and commitments involved in being an active and positively engaged citizen), or intellectual character (e.g., attributes such as love of learning, seeking truth, creativity, and intellectual humility) -have been the focus of OST youth development programs, either wholly (e.g., through character education programs) or as outcomes of efforts to enhance other facets of thriving (Berkowitz, 2011(Berkowitz, , 2012Hilliard et al, 2014;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%